Solusi Persamaan Panas Dimensi Satu dengan Metode Transformasi Laplace dan Transformasi Elzaki - Zaki, Ahmad; Syam, Rahmat; Lubis, Kristina (Journal of Mathematics, Computations and Statistics, 2022)
This study aims to determine the solution to the one dimensional heat equation using the Laplace transformation and Elzaki transformation. This research is a pure research that examines the Laplace transformation and Elzaki transformation in the one dimensional heat equation